Luminescence spectroscopy and near-infrared to visible upconversion in Er3+ and Yb3+ codoped Sc2O3 nanoparticles. (October 2017) - Wang, Chengli; Chen, Xin; Xie, Meng; Lin, Hai; Zhou, Yanyan; Liu, Lina; Li, Chun; Zeng, Fanming
Graphical abstract: Highlights: The Er 3+, Yb 3+ co-doped Sc2 O3 nanoparticles show a high pure red emission and the red to green intensity ratio is up to 56.43. The great enhancement of red emission can be explained by analyzing energy transfer processes in Sc2 O3 host. near linear laser power dependence of 662 nm emission can be illustrated based on steady-state rate equations. Abstract: The Er 3+ and Yb 3+ co-doped Sc2 O3 nanoparticles were prepared by co-precipitation method. The phase structure and up-conversion properties were investigated using XRD, FESEM and up-conversion spectra. The nanoparticles with the size of about 40 nm emitted red and green light. Yb 3+ ions are crucial to adjust the intensity proportion of red and green emission as a sensitizer. In Er 3+, Yb 3+ co-doping samples, the red emissions are much higher than green and the intensity ratio is up to 56.43, while the green to red intensity ratio is 11.21 with Er 3+ single doping, which both show excellent mono-chromaticity. Strong red emissions are attributed to the cross-relaxation energy transfer and energy back-transfer processes. High Yb 3+ ions concentrations induce the red up-conversion saturation, resulting in a near linear laser power dependence, and it can be illustrated based on steady-state rate equations.